Elastic strains influence during GaSb/InAs heteroepitaxy from liquid phase - Shutov, S.V.; Baganov, Ye.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Influence of strains that appear in GaSb/InAs heterosystem on heteroepitaxial layer planarity is considered. It is shown that minimal supercooling of solution-melt at the saturation temperature of gallium antimonide in gallium melt 450 ºC is 7.8 ºС for [111] and 5.8 ºС for [100] growth directions. Calculated are the minimal growth rate 22 nm/s that is necessary for prevention of distortion appearance of epitaxial layer surface caused by elastic strains and the critical thicknesses of misfit dislocation formation – 50 and 54 nm for the [100] and [111] growth directions, respectively. It is shown experimentally that the lack of minimal supercooling leads to the island growth mode.